A radiation of hydrobiid snails in the caves and streams at Precipitous Bluff, southwest Tasmania, Australia (Mollusca: Caenogastropoda: Rissooidea: Hydrobiidae s.l.) - Ponder, W. F.; Clark, S. A.; Eberhard, S.; Studdert, J. B. (Zootaxa, 2005)
A radiation of hydrobiid snails is described from caves at Precipitous Bluff, southern Tasmania. The radiation (10 species) comprises two closely related genera; Pseudotricula, endemic to the Precipitous Bluff caves, and Nanocochlea found in these caves and surface streams and seepages, but also known from elsewhere in southern Tasmania. Two Precipitous Bluff species of Nanocochlea inhabit streams outside the caves, while one is found within the caves; all three are new. Seven species of Pseudotricula are described, six being new. Up to five species, one Nanocochlea and four Pseudotricula, are found in single stream habitats characterised by diverse sediment and slow to moderate flows. One Pseudotricula species is found in a swifter, larger stream with cobbles and gravel and another on smooth limestone surfaces in fast flowing water and water falls. A cladistic analysis (based on morphology) confirmed the monophyly of Pseudotricula, but the monophyly of Nanocochlea is less robust.